The Effect of Incentives and Work Stress on Employee Performance During the Covid-19 Pandemic in PTPN IV Kebon Tanah Raja - Fajar Rezeki Ananda Lubis (Enrichment : Journal of Management, 2021)
The purpose of this study is to determine the effect of incentives and work stress on employee performance during the COVID-19 pandemic.The present study was carried out in PTPN IV KEBON TANAH RAJA. The sample in this study consisted of 51 employees.Data was collected using a questionnaire in accordance with the indicators of each variable used. The data obtained were then analyzed using multiple linear regression analysis.The results show that incentives and work stress simultaneously have a significant effect on employee performance during the COVID-19 pandemic.The results of the t-test indicate that incentives and job stress have a significant effect on employee performance. The incentive factor has a more dominant effect on employee performance compared to job stress.